2006
DOI: 10.1002/nur.20146
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic and generational influences on emotional distress and risk behaviors among Chinese and Filipino American adolescents

Abstract: The purpose of this study was to explore ethnic and generational influences among Chinese, Filipino, and Euro American adolescents on emotional distress and risk behaviors. Hierarchical multiple regression analyses were conducted with 216 Chinese, 387 Filipino, and 400 Euro American adolescents from the National Longitudinal Study on Adolescent Health to investigate the influence of ethnicity on depression, somatic symptoms, delinquency, and substance use; and to examine the influence of generation on the outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 43 publications
1
57
0
3
Order By: Relevance
“…Congruent with our results, Shrake and Rhee found that Korean American adolescents had high levels of anxiety/depression and social problems and low levels of rulebreaking behavior. These findings are also consistent with previous results of ethnic group comparisons, indicating that Asian American adolescents had more anxiety disorders and social problems but less delinquent behavior than European American adolescents, although some Asian American subgroup differences were found (Lorenzo, Frost, & Reinherz, 2000;Nguyen et al, 2004;Willgerodt & Thompson, 2006;Yeh, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…Congruent with our results, Shrake and Rhee found that Korean American adolescents had high levels of anxiety/depression and social problems and low levels of rulebreaking behavior. These findings are also consistent with previous results of ethnic group comparisons, indicating that Asian American adolescents had more anxiety disorders and social problems but less delinquent behavior than European American adolescents, although some Asian American subgroup differences were found (Lorenzo, Frost, & Reinherz, 2000;Nguyen et al, 2004;Willgerodt & Thompson, 2006;Yeh, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…However, epidemiological surveys show that relatively few parents (approximately 14%) participate in any form of parent education and exposure to evidence based intervention is lower (Sanders et al 1999). Parents from culturally diverse backgrounds are even less likely than other families to access parenting programs (Cunningham et al 2000;Katz et al 2007;Sawrikar and Katz 2008) and this is despite the fact that culturally diverse children can be at a greater risk for developing behaviour problems (McCabe et al 2005;McKay et al 1996;Willgerodt and Thompson 2006).…”
Section: Introductionmentioning
confidence: 95%
“…There is documentation indicating that Asian children were more likely to make somatic complaints than non-Asian groups (Greenberger & Chen, 1996;Willgerodt & Thompson, 2006). The participants in this study also scored a marginally significant level in somatisation.…”
Section: Effects Of Language Skillsmentioning
confidence: 68%